Performance is Affected by Planning and Reflection - Katsuhiko NAGASE (AAOS Transactions)
The present study examined the effects of planning and reflection on performance. Ninety-four undergraduate participants responded to the three online questionnaires. Questionnaire 1 (Q1) was placed three weeks before the exam of Decision Making. Questionnaire 2 (Q2) was placed a week before the exam. Questionnaire 3 (Q3) was placed within the exam. Two attributes of the plan were investigated. One is the planned preparation time for the exam(PT), and the other is the detailedness of the plan(DP). Related questions were included both in Q1 and Q2. One of the questions of Q3 was, “Describe the gap between the preparation plan for the exam and its execution.” Reflection (RF) was measured by the number of characters of the response to that question. Structural equation modeling (SEM) revealed that PT significantly acted on the preparation time, and preparation time significantly acted on the performance (exam score). DP did not significantly affect preparation time, so it did not affect performance consequently. RF slightly affected performance (p=.09). The model fit statistics indicated GFI=.993, AGFI=.949, and RMSEA=0.